2022
DOI: 10.1186/s12943-022-01519-7
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase like 7B is a potential therapeutic target for reversing EGFR-TKIs resistance in lung adenocarcinoma

Abstract: Background Identification of potential novel targets for reversing resistance to Epidermal Growth Factor Receptor (EGFR)-tyrosine kinase inhibitors (EGFR-TKIs) holds great promise for the treatment of relapsed lung adenocarcinoma (LUAD). In the present study, we aim to investigate the role of methyltransferase-like 7B (METTL7B) in inducing EGFR-TKIs resistance in LUAD and whether it could be a therapeutic target for reversing the resistance. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Recently, Song et al. reported that METTL7B in lung adenocarcinoma reversed resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors by changing m6A modification ( 54 ). As a new molecule in glioma, we demonstrated that METTL7B participates in the cellular immune response by affecting the mRNA stability of PD-L1 and showed the critical role of m6A in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Song et al. reported that METTL7B in lung adenocarcinoma reversed resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors by changing m6A modification ( 54 ). As a new molecule in glioma, we demonstrated that METTL7B participates in the cellular immune response by affecting the mRNA stability of PD-L1 and showed the critical role of m6A in this process.…”
Section: Discussionmentioning
confidence: 99%
“… 423 Similarly, METTL7B can increase the expression of GPX4, HMOX1, and SOD1 by m6A modification, leading to ferroptosis resistance and TKI resistance in LUAD (see Ferroptosis). 424 Moreover, METTL-KIAA1429 can enhance homeobox A1 (HOXA1) mRNA stability and lead to gefitinib resistance in NSCLC through HOXA1 expression, 425 but HOXA1 is considered an oncogene whose function is currently unknown. The m6A modification mediated by YTH N6-methyladenosine RNA binding protein 2 (YTHDF2) can increase circRNA-ASK1 degradation, thereby attenuating the inhibitory effect of the circRNA-ASK1-encoded product ASK1-272a.a on AKT pathway and increasing LUAD resistance to gefitinib.…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%
“…Aberrant regulation of m6A modification affects lung cancer prognosis and afatinib resistance ( 86 ). In LUAD, METTL7B is a potential therapeutic target for reversing gefitinib- and osimertinib-resistance by promoting three key reactive oxygen species scavengers (ROS) ( 87 , 88 ).The dysregulation of the FTO-m6A axis in leukemia cells is required for EGFR-TKI (tyrosine kinase inhibitors) resistance, which can be prevented or eradicated by specifically targeting FTO ( 89 ). In chronic myelogenous leukemia (CML), METTL3, and METTL14 are upregulated and affect sensitivity to TKI imatinib ( 90 ).…”
Section: Aberrant Regulation Of M6a Modification In Drug Resistancementioning
confidence: 99%